2020
DOI: 10.3389/fpsyg.2020.01558
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Venture Capital on Enterprise Benefit According to the Heterogeneity of Human Capital of Entrepreneur

Abstract: This research was conducted for the purpose of exploring the role of venture capital (VC) based on the heterogeneity of human capital in the process of transforming innovation capabilities of enterprise into enterprise benefits and providing a reference for further research on enterprise performance development. In this study, 399 listed companies that obtained VC before 2018 from the China VC database and Wind China financial database were selected as research objects, and relevant data of patent number, retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
(37 reference statements)
0
8
0
1
Order By: Relevance
“…Esta situación es semejante a la encontrada a nivel mundial, en donde solo el 18% de las pymes o inventores individuales solicitan una patente: 72% son grandes empresas, 10% universidades y organizaciones públicas (European Patent Office, 2020). Las patentes en las empresas, según Jin et al (2020) se relacionan con el nivel de educación de los empleados y con la proporción de profesionales de la ingeniería, teniendo en cuenta que este tipo de profesionales prestan más atención a la Investigación y Desarrollo junto con la innovación tecnológica de las empresas, proporcionando servicios profesionales con valor agregado. De esta manera mejora la capacidad de innovación de las empresas, lo que permite que puedan sobrevivir en el mercado, ir más allá de sus capacidades y resistir a las amenazas del entorno.…”
Section: Resultsunclassified
“…Esta situación es semejante a la encontrada a nivel mundial, en donde solo el 18% de las pymes o inventores individuales solicitan una patente: 72% son grandes empresas, 10% universidades y organizaciones públicas (European Patent Office, 2020). Las patentes en las empresas, según Jin et al (2020) se relacionan con el nivel de educación de los empleados y con la proporción de profesionales de la ingeniería, teniendo en cuenta que este tipo de profesionales prestan más atención a la Investigación y Desarrollo junto con la innovación tecnológica de las empresas, proporcionando servicios profesionales con valor agregado. De esta manera mejora la capacidad de innovación de las empresas, lo que permite que puedan sobrevivir en el mercado, ir más allá de sus capacidades y resistir a las amenazas del entorno.…”
Section: Resultsunclassified
“…However, in Brazil, digital practices start to be implemented in large cities and then spread in small and medium urban centers (Cunha, Przeybilovicz et al 2016 ). In addition, the training of managers has a very important role in this scenario, and they are responsible for directing their teams towards innovation (Jin, Zheng et al 2020 ). They are the key to the success of digital transformation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…But again, there is evidence of the replacement of CEOs, which seemed to have no well in the eyes of the founder entrepreneurs. While Jin et al (2021) showed that VC-backed firms are more successful owing to VC firms' entrepreneurial skills, motivations, and strategy. While entrepreneurs yearn for most strategic value-added assistance, especially in the form of financial support and networking advice given by VC investors, again they are unclear about guidance regarding inner organisation problems.…”
Section: H2: Vc Firms Are the Central Drivers Of Evolving Early-stage...mentioning
confidence: 99%